Sosialisasi Green school untuk Mendukung Ketahanan Pangan melalui Pertanian Organik di SMK Pandanaran Boyolali : Penelitian - Husain Fahri Singo Wijaksono; Hizkia Avandewsa Putu Surya Al Whamesya; Hilda Wulandari; Unna Ria Safitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity was conducted to improve students’ understanding of Green School concepts and local food security through organic farming at SMK Pandanaran, Boyolali. The program involved 32 students from grades X and XI and was implemented through educational socialization and interactive discussions linking Green School principles with school environmental management and organic farming as part of local food security education. The activity focused on material presentation, two-way discussions, and student reflection on environmental and food security issues. Evaluation was carried out through observation of student participation, oral and written reflections, and service team notes. The results indicated improved student understanding of Green School principles, increased awareness of local food security, and the ability to relate organic farming concepts to environmental and social aspects. This activity encouraged active student participation and provided opportunities for the development of sustainable environmental education programs through the integration of school ga